64. Acute flaccid paralysis by Enterovirus D68 infection: First Italian description on adult patient and role of electrophysiology. Issue 12 (December 2017) - Ceccanti, M.; Rubino, A.; Romanzi, F.; Onesti, E.; Tartaglia, G.; Inghilleri, M.
Abstract : A Peruvian woman was admitted to the Emergency Department of "Policlinico Umberto I" in Rome for drop head associated to an acute flaccid paralysis of the upper limbs, beginning from the proximal muscles and rapidly extending to the distal. No sensory involvement was objectified. Her clinical history was significant for Non-Hodgkin Lymphoma and hematopoietic stem cell transplantation, complicated with a chronic graft-versus-host disease. Medullar spinal cord MRI showed a long tract of T2 hyperintensity in the anterior and central region of the cervical cord, with an elective involvement of grey matter. Lumbar puncture showed pleocytosis. An early NCS and EMG exam demonstrated reduction in cMAP amplitude from Ulnar and Median nerves bilaterally with absence of F-waves, with normal sensory conduction. Phrenic nerve assessment revealed bilateral reduction in amplitude. Severe reduction in spatial recruitment, doublets and triplets were also detected in the needle examination of upper limbs. Normal SEP were registered. Entherovirus D68, a polio-like virus firstly isolated in US in 2014, was isolated in patient's cerebrospinal fluid, plasma and throat swab. Intravenous immunoglobulins, together with steroids and Acyclovir, were dispensed as replacement therapy and passive immunization, with no effect. Patient underwent to tracheostomy and died after two weeks from hospitalization.